130k views
2 votes
Given the functions f(x)=2x^2-3x-8 and g(x)=3x2+5x+1

Given the functions f(x)=2x^2-3x-8 and g(x)=3x2+5x+1-example-1

1 Answer

3 votes

Answer:

B

Explanation:

the product (2x² - 3x - 8)(3x² + 5x + 1) is required

multiply each term in the second factor by each term in the first factor.

= 2x²(3x² + 5x + 1) - 3x(3x² + 5x + 1) - 8(3x² + 5x + 1) ← distribute

= 6
x^(4) + 10x³ + 2x² - 9x³ - 15x² - 3x - 24x² - 40x - 8

collecting like terms gives

6
x^(4) + x³ - 37x² - 43x - 8 → B


User Peter Wagener
by
6.0k points